Contested psychiatric ontology and feminist critique: ‘Female Sexual Dysfunction’ and the Diagnostic and Statistical Manual - Angel, Katherine (History of the Human Sciences, 2012)
In this article I discuss the emergence of Female Sexual Dysfunction (FSD) within American psychiatry and beyond in the postwar period, setting out what I believe to be important and suggestive questions neglected in existing scholarship. Tracing the nomenclature within successive editions of the American Psychiatric Association’s Diagnostic and Statistical Manual (DSM), I consider the reification of the term ‘FSD’, and the activism and scholarship that the rise of the category has occasioned. I suggest that analysis of FSD benefits from scrutiny of a wider range of sources (especially since the popular and scientific cross-pollinate). I explore the multiplicity of FSD that emerges when one examines this wider range, but I also underscore a reinscribing of anxieties about psychogenic aetiologies. I then argue that what makes the FSD case additionally interesting, over and above other conditions with a contested status, is the historically complex relationship between psychiatry and feminism that is at work in contemporary debates. I suggest that existing literature on FSD has not yet posed some of the most important and salient questions at stake in writing about women’s sexual problems in this period, and can only do this when the relationship between ‘second-wave’ feminism, ‘post-feminism’, psychiatry and psychoanalysis becomes part of the terrain to be analysed, rather than the medium through which analysis is conducted.
Keywords: 1900-1999; 1970-1979; 1980-1989; 1990-1999; amérique du nord; amériques; approches et analyses; cours; discipline; discours dominant; europe; postmodernisme; premier cycle; périodes historiques; régions géographiques; santé; sciences humaines; sexisme; soc2051; sociologie; systèmes d'oppressions; thématiques; violences; états-unis

United in anger: a history of ACT UP - Hubbard, Jim; Schulman, Sarah; ACT UP Oral History Project; United in Anger, Inc (United in Anger, Inc., 2012)
"A unique feature-length documentary that combines startling archival footage that puts the audience on the ground with the activists and the remarkably insightful interviews from the ACT UP Oral History Project to explore ACT UP (the AIDS Coalition to Unleash Power) from a grassroots perspective - how a small group of men and women of all races and classes, came together to change the world and save each other's lives."
Keywords: 1900-1999; 1980-1989; LGBTQIA2+; act up; amériques; approches et analyses; cinéma; communication; cours; discipline; documentaire; film; intersectionnalité; militance; premier cycle; périodes historiques; queer; régions géographiques; santé; sexualité; soc2014; thématiques; états-unis